Fish on the move : fishing between discourses and borders in the Northern Adriatic - Rogelja, Nataša; Janko Spreizer, Alenka (Springer, 2017)
This book analyses the relation between different discourses and actors through an ethnographic approach, showing not only how fishermen in Slovenia respond to international political economy, how they struggle to survive but also how they generate small changes. Fishing in the northeastern part of the Adriatic Sea makes for a substantial economy anchored in many stories. Regional conflicts, wars, the demise of empires and the rise of nation states with ensuing maritime border issues, socialist heritage, transnational and transformational processes in Europe, and the growth of capitalist relations between production and consumption in coastal areas, have all contributed to the specific discourses that have affected this relatively under-researched area. How this complex, layered and ambiguous quarrelling is constituted at different levels and how this situation is lived and experienced by the local fishermen working along the present Slovene coast effectively forms the core of this book.
Keywords: Fisheries -- Adriatic Sea.; Fishing -- Adriatic Sea.; Mediterranean Sea -- Adriatic Sea.; elektronické knihy; electronic books